The effect of job satisfaction, organizational communication, work environment, and work motivation on the churchs employee performance - Jonathan Charmian Vivaldy; Nagian Toni (BISMA (Bisnis dan Manajemen), 2020)
This study aims to determine the effect of job satisfaction, organizational communication, work environment, and work motivation on the performance of big family of Indonesian Bethel Church Medan Plaza's employees both simultaneously and partially. The primary data is obtained by distributing questionnaires to all employees of the big family of Indonesian Bethel Church Medan Plaza. Data analysis was carried out by descriptive analysis, classical assumption test, and hypothesis test by multiple linear regression method. The result concludes that job satisfaction, organizational communication, work environment, and work motivation simultaneously affect employee performance. This research is expected to enrich the study of human resource management on the factors that influence performance in religious-based organizations that have not been widely studied in Indonesia.